2022
DOI: 10.1111/1750-3841.16193
|View full text |Cite
|
Sign up to set email alerts
|

Interaction mechanism between ZnO nanoparticles‐whey protein and its effect on toxicity in GES‐1 cells

Abstract: The interaction between zinc oxide nanoparticles (ZnO NPs) and whey protein (WP) was studied. The gastric epithelial cell line (GES‐1) was used to evaluate the toxicity intensity of ZnO NPs. The interaction mechanism of ZnO NPs and WP was studied by spectroscopic techniques. The results showed that the inhibitory effect of ZnO NPs on cells activity could be reduced when added to ZnO NPs at a concentration of 50 µg/ml. The fluorescence quenching mechanism of ZnO NPs on WP is a combination of dynamic and static … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
3
1
Order By: Relevance
“…In our study, in some cases, alum was found to be more effective than SFNPs, which could be due to the formation of antigen depots that gradually release antigen [25] or due to the impact of nanoparticles encapsulation (SFNPs) on protein conformation. [26,27] In addition, the previous studies have reported enhanced antibody responses with alum, [13,28] whereas our study showed a significant Th1 response that can be due to the presence of immunodominant T-cell epitopes in the designed multi-epitope protein.…”
Section: Discussioncontrasting
confidence: 59%
“…In our study, in some cases, alum was found to be more effective than SFNPs, which could be due to the formation of antigen depots that gradually release antigen [25] or due to the impact of nanoparticles encapsulation (SFNPs) on protein conformation. [26,27] In addition, the previous studies have reported enhanced antibody responses with alum, [13,28] whereas our study showed a significant Th1 response that can be due to the presence of immunodominant T-cell epitopes in the designed multi-epitope protein.…”
Section: Discussioncontrasting
confidence: 59%
“…The hydrophobic Trp residues and hydrophilic Tyr residues were the main sources of endogenous fluorescence when the excitation wavelength was 280 nm. 48 Fluorescence emission spectrum of LuxS is shown in Figure 6A , with a strong emission peak at 286 nm. With the increase of BAI concentration, the endogenous fluorescence of LuxS gradually weakened, and it shows that BAI interacts with LuxS and quenches the endogenous fluorescence of LuxS.…”
Section: Resultsmentioning
confidence: 99%
“…[36,37] Furthermore, there are some evidences, indicating a beneficial interaction between proteins and ZnO. [38][39][40][41] However, the protein-assisted in situ synthesis of ZnO in NR latex remains unreported.…”
Section: Introductionmentioning
confidence: 99%